Pattern of Industrial Growth and Revolutions - Hussain, T.; Aziz, M. H. (The Nucleus, 2018)
The world begun industrial development in eighteenth century and experienced four industrial revolutions which made a huge impact on economic growth. Those countries rise as an economic power which adopt and worked on advance technology in each industrial revolution. Advent of technology could be attributed to chance, choice or crises that could be either disruptive or sustaining in nature. We have used two theories to discuss the growth pattern of economy named as: Theory of long waves and Theory of production revolutions. Kondratieff and Juglar cycles have applied to map each revolutions along with its elements that have prevailed the economy. There is a link between industrial growth patterns and GDP. Further, these revolutions have three phases (pre, during and post revolution) which effect the micro, meso and macro level in both positive and negative way. However, as far as overall industrial development cycle is concerned, theory of production revolution proposes that we are now in the intermediate phase of industrial growth and most probably its falling phase will start in 2070. Moreover, theory of long waves suggest that fourth revolution is now in rising phase and will reach to peak in coming 50-60 years in the form of decentralized self-regulating system. Circumstances suggest that increase of autonomous system and bio-technology will raise unemployment along with life expectancy. As a result, world might face safety, security, health, food and accommodation issues. Industries will tend towards micro-economy and they may face reliability, data security, employee loyalty and flexibility problems. According to corresponding relationship of industrial growth and revolution, we expect that next industrial revolution would be crises based and bio-technology would concentrate on control of human’s emotions. Scientific progress and research will enhance due to the rise of Quantum Informatics.